The syntaxic structure of the subject Ontological analysis - Khadri, Nouri (Milev Journal of Research and Studies, 2017)
This research aims to identify the connection between the subject and its interrelations with other syntactic elements included in the Arabic sentence; this understanding is based on Arabic grammar and functional grammar. The present article is not restricted only to the description of the subject positions within the subject network analysis but it rather sets out to arrive at semantic web.